Learning Methods Used by Arabic Language Teachers during the New Normal Period of COVID-19 - Arenaz Tania; Milton Alan; Xuemin Pik (Yayasan Adra Karima Hubbi, 2023)
The attention of language learning experts conducting various research and studies to determine the effectiveness and success of Arabic learning methods. Communication strategy is one of the strategies used in learning Arabic, which focuses on communication skills. This strategy is used in an analysis that uses a literature strategy where the data is based on various significant reference sources in this discussion. The results of this study indicate that learning methods based on the communicative approach emphasize listening and speaking skills; the learning objectives to be achieved through these various methods are so that students can communicate in the target language being studied whenever and wherever that is. Suitable for language learning. Arabic language education research has reviewed a lot about learning at the elementary, middle, and high school education levels, most of which show theoretical and practical aspects. This study aims to reveal the application of PAUD Arabic education theory and look at the strategies used by teachers or schools and things that influence the initial inculcation of Arabic language learning in early Childhood by using vocabulary strategies.